Quenching the collective effects on the two-photon correlation from two double-raman atoms - Ooi, Chong Heng Raymond (2007)
We obtain an analytical expression for two-photon correlation G((2)) from two atoms driven in a double-Raman (or Lambda) configuration where collective effects such as superradiant, subradiant, and dipole-dipole interaction are included. It is found that the collective effects on the G((2)) can be quenched to some extent by a resonant control laser field. The collective effects provide features via G((2)) that enable the two atoms to be resolved at subwavelength separation. We also identify an effect in the double Raman scheme due to the collective effects and the control field, i.e., the Stokes and anti-Stokes frequencies are increased by fourfold.